Comparative evaluation of histopathological analysis, KOH wet mount and fungal culture to diagnose fungal infections in post-COVID patients - Seema N. Baxi; Mayuri R. Gohil; Anamika J. Navadiya; Mayuri K. Bapodra; Hiral R. Patel (Indian Journal of Pathology and Microbiology)
Context and Aim: There is increasing prevalence of post-COVID fungal infection of rhinoorbitocerebral region especially mucormycosis and aspergillosis in India.[1] Early diagnosis of these fungal infections are of utmost importance, since it may improve outcome and survival.[2-8] The objective of this study was to evaluate and compare routine laboratory diagnostic methods, that is, histopathological examination, KOH wet mount and fungal culture in the diagnosis of post-COVID fungal infections. Materials and Methods: A total of 106 specimens of clinically suspected patients of post-COVID fungal infection of rhinoorbitocerebral region received in histopathology department were included in this study. The data of KOH wet mount and culture were acquired from the microbiology department after histopathological examination. Result: Approximately 88.68% of patients were diagnosed having fungal infections by one of the laboratory methods. The sensitivity of histopathological examination was highest (79.78%), followed by KOH wet mount (58.51%) and fungal culture (35.10%). Rhizopus species of zygomycetes group were the most common isolate (24.24%) on SDA culture. Overall 76% concordance was found between histopathological examination and fungal culture report for morphological identification of fungi. Conclusion: For the diagnosis of post-COVID fungal infection of Rhino-orbito-cerebral region, histopathological examination is was found to be more sensitive and rapid method to detect fungal hyphae. It leads to early treatment, prevents morbidity and mortality.